Government enterprise: a comparative study - Friedmann, Wolfgang; Garner, J. F.; United Kingdom National Committee of Comparative Law.; British Institute of International and Comparative Law. (London: Stevens, 1970)
This book is on public corporation which have been a feature of nationalism. It is hoped to evoke new anxieties and to produce a few more insights into the way others were facing the modern problems of public enterprise.
"Based on the work of a colloquium ... held at the University of Cambridge in September 1968 and organised by the United Kingdom National Committee of Comparative Law, with the assistance of the British Institute of International and Comparative Law."
Includes bibliographical references and index.
oo 13/09/2018
Loans
Keywords: Government corporations; Government business enterprises